Knowledge about food safety and handling practices - Lessons from the Serbian public universities - Vuksanović Nikola; Demirović Bajrami Dunja; Petrović Marko D.; Jotanović Raletić Saša; Radivojević Goran (Sciendo, 2022)
Education about food safety is important for public health, and the best place to provide it is a university environment. The aim of the research was to assess food safety knowledge and self-reported food handling practices among students in Serbia.